Responsive Parenting and Friendship Quality in Adolescents: Interpersonal Communication Skills as a Mediator - Mahirah, Aaliya Hana; Sampe Tondok, Marselius (Bulletin of Counseling and Psychotherapy, 2024)
Existing knowledge indicates that responsive parenting significantly influences the quality of friendships among adolescents. However, previous research has not fully elucidated the dynamics within the relationship between responsive parenting and friendship quality. This study seeks to investigate the role of interpersonal communication skills as a mediator in relationships between responsive parenting and friendship quality. It involved 150 respondents aged 12-20 years (Mage = 16.87; SD = 2.51), comprising 50 early adolescents, 50 middle adolescents, and 50 late adolescents. Measurement of the three variables utilized scales: the Parental Responsiveness Scale subscale, the Interpersonal Communication Scale, and the McGill Friendship Questionnaires-Friend's Functions. Hypothesis testing using mediation analysis reveals that interpersonal communication skills mediate the relationship between father/mother's responsive parenting and friendship quality. These findings suggest that positive interactions between parents and adolescents through responsive parenting serve as models for adolescents in their peer relationships by enhancing interpersonal communication skills. The limitations and directions for further research are discussed.